Medication following bariatric surgery for type 2 diabetes mellitus (BY-PLUS) study: rationale and design of a randomised controlled study - Alexander Dimitri Miras; Carel le Roux; Alexis Sudlow; Ricardo Vitor Cohen; Hassan Kahal; Dimitri J Pournaras; Jill Townley; Helen Heneghan (BMJ Open)
Introduction Bariatric surgery is an effective method of controlling glycaemia in patients with type 2 diabetes mellitus (T2DM) and obesity. Long-term studies suggest that although glycaemic control remains good, only 20%–40% of patients will maintain remission according to the American Diabetes Association criteria.Purpose This trial aims to examine the safety and efficacy of combining Roux-en-Y gastric bypass or sleeve gastrectomy with goal-directed medical therapy to improve long-term glycaemic control of T2DM.Methods and analysis This prospective, open-label multicentre randomised controlled trial (RCT) will recruit 150 patients with obesity and T2DM from tertiary care obesity centres. Patients will be randomised 1:1 to receive either bariatric surgery and standard medical care or bariatric surgery and intensive goal-directed medical therapy, titrated to specific targets for glycated haemoglobin (HbA1c), blood pressure (BP) and low-density lipoproteins (LDL) cholesterol. The primary endpoints are the proportion of patients in each arm with an HbA1c<6.5% (48 mmol/mol) at 1 year and the proportion of patients in each arm achieving the composite endpoint of HbA1c<6.5% (48 mmol/mol), BP<130/80 mm Hg and LDL<2.6 mmol/L at 5 years.Ethics and dissemination The local institutional review board approved this study. This study represents the first RCT to examine the safety and efficacy of combining bariatric surgery with intensive medical therapy compared with bariatric surgery and usual care for long-term diabetes control.Trial registration number NCT04432025.